2023
DOI: 10.1001/jamainternmed.2023.1838
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Physician and Artificial Intelligence Chatbot Responses to Patient Questions Posted to a Public Social Media Forum

Abstract: ImportanceThe rapid expansion of virtual health care has caused a surge in patient messages concomitant with more work and burnout among health care professionals. Artificial intelligence (AI) assistants could potentially aid in creating answers to patient questions by drafting responses that could be reviewed by clinicians.ObjectiveTo evaluate the ability of an AI chatbot assistant (ChatGPT), released in November 2022, to provide quality and empathetic responses to patient questions.Design, Setting, and Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

13
269
1
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 988 publications
(419 citation statements)
references
References 23 publications
13
269
1
3
Order By: Relevance
“…Even if this were achieved, at the present time, AI cannot replicate in-person, human-to-human empathy. A recent study suggested that the AI chatbot was more empathetic than physicians, but an important caveat was this study considered only written interactions . Most patients want their treating clinician to be accurate in their diagnosis but also empathetic during verbal and in-person communication.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Even if this were achieved, at the present time, AI cannot replicate in-person, human-to-human empathy. A recent study suggested that the AI chatbot was more empathetic than physicians, but an important caveat was this study considered only written interactions . Most patients want their treating clinician to be accurate in their diagnosis but also empathetic during verbal and in-person communication.…”
mentioning
confidence: 99%
“…ChatGPT, a generative artificial intelligence (AI) chatbot, has recently been hailed as a promising tool to improve health care quality. One study compared output from the AI chatbot for medical questions with answers from physicians; other studies have evaluated the AI chatbot’s responses to sample clinical vignettes . A foundational aspect of high-quality health care—making a correct and timely diagnosis—remains a challenge in modern medicine despite decades of technological advances .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These tools have rekindled enthusiasm for AI-powered health care . Chatbot answers to health care questions often compare favorably to those of other medical resources . Moreover, chatbots can save time by taking on repetitive tasks that contribute to clinician burnout.…”
mentioning
confidence: 99%
“…Perhaps of greatest concern is the need to remain wary about public perceptions of chatbots’ expanding lists of qualifications to avoid false confidence in the AI chatbot as the latest AI physician. A recent study compared the advice of physicians and a chatbot when responding to medical questions posted on an internet forum and found that the chatbot outperformed physicians in both empathy and quality scores . The authors appropriately emphasized relevant limitations of their study, noting that internet chat forums may not reflect real patient-physician interactions and that general clinical questions do not cover the full spectrum of reasons for consulting a physician.…”
mentioning
confidence: 99%